2016
DOI: 10.1002/mdc3.12419
|View full text |Cite
|
Sign up to set email alerts
|

PLA2G6 ‐Associated Neurodegeneration: Report of a Novel Mutation in Two Siblings with Strikingly Different Clinical Presentation

Abstract: Neurodegeneration with brain iron accumulation (NBIA) comprises a group of hereditary heterogeneous disorders (most of them autosomal recessive) characterized by the presence of an extrapyramidal progressive dysfunction and excess iron accumulation in different locations in the brain. Overall, it remains unclear whether increased brain iron content, documented in many neurodegenerative diseases, is a direct cause of neurodegeneration, a secondary event in a pathophysiologic cascade, or just a nonspecific marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Most important useful handles in guiding diagnosis with the herein proposed clinical algorithms for dystonia‐ataxia syndromes include the age of disease onset, some associated clinical clues and particular imaging findings. However, major criticism to clinical algorithms arise on the clinical and genetic heterogeneity (e.g., many entities or combined syndromes are not distinct conditions), but may represent a continuum between different phenotypes, as is the case for ATP1A3‐, or PLA2G6‐related disorders . In addition, clinical algorithms may not fit for atypical phenotypes or be useless if they are too simplistic or rigid, as they may delay or obstruct the identification of the underlying genetic cause in a determined patient .…”
Section: Discussionmentioning
confidence: 99%
“…Most important useful handles in guiding diagnosis with the herein proposed clinical algorithms for dystonia‐ataxia syndromes include the age of disease onset, some associated clinical clues and particular imaging findings. However, major criticism to clinical algorithms arise on the clinical and genetic heterogeneity (e.g., many entities or combined syndromes are not distinct conditions), but may represent a continuum between different phenotypes, as is the case for ATP1A3‐, or PLA2G6‐related disorders . In addition, clinical algorithms may not fit for atypical phenotypes or be useless if they are too simplistic or rigid, as they may delay or obstruct the identification of the underlying genetic cause in a determined patient .…”
Section: Discussionmentioning
confidence: 99%
“…10 There are reports of pigmentary retinopathy in the PLA2G6 mutation, and the underlying cause could be decreased rate of proliferation of retinal cells attributed to inhibited activity of iPLA2-VIA. 11 Retinal vasculitis is a potential sight-threatening inflammatory eye condition and can occur as an isolated idiopathic condition, as a manifestation of infectious disease, or as a part of systemic immune-mediated disease. 12 To the best of our knowledge, retinal vasculitis has not been described in PLAN.…”
mentioning
confidence: 99%
“…Two recent case series have now demonstrated that syndromes caused by biallelic mutations in phospholipase A2 group VI ( PLA2G6 ) (Online Mendelian Inheritance in Man no. 60360) also are examples of this general insight.…”
mentioning
confidence: 99%
“…• X-linked Charcot-Marie-Tooth disease type 5 (CMTX5), Arts syndrome, and nonsyndromic sensorineural deafness (DFN2) are continuous allelic phenotypic clusters caused by phosphoribosyl pyrophosphate synthetase 1 (PRPS1) mutations. 8 Two recent case series 9,10 have now demonstrated that syndromes caused by biallelic mutations in phospholipase A2 group VI (PLA2G6) (Online Mendelian Inheritance in Man no. 60360) also are examples of this general insight.…”
mentioning
confidence: 99%